KRAS mutations: efficacy and sensitivity of early predictive screening of cancer progression require other gene mutations in addition to KRAS - Sambi, Manpreet; Szewczuk, Myron R. (Translational Cancer Research, 2017)
The KRAS gene, also known as Kristen rat sarcoma viral oncogene homolog, is a member of the Ras family of cell proliferation regulators and plays an important role in cancer progression upon the mutation induced activation of this gene (1). A significant role that they play is in a cell proliferation signaling cascade that involves receptor to nucleus signal transduction and therefore the activation of this pathway is under tight control (1,2).